Number sense and academic buoyancy among middle school students: A serial mediation model of mathematical metacognition awareness and math anxiety - Aksu, Zeki; Kul, Ümit; Satıcı, Seydi Ahmet (Anales de Psicología / Annals of Psychology, 2024)
The present study examined whether number sense was related to academic buoyancy and whether this relationship was mediated by mathematical metacognition awareness and mathematics anxiety. Data was gathered from 231 students in grade 7 and 8 middle schools through self-report measures of number sense, academic buoyancy, metacognition awareness, and math anxiety. The results revealed a significant positive association between number sense and mathematical metacognition awareness, as well as a significant negative association between number sense and math anxiety. Moreover, results indicated that number sense facilitated academic buoyancy via mathematical metacognition awareness and then math anxiety. These findings contribute to the understanding of how these factors may impact academic buoyancy in middle school students.